NOTE ON THE CONTROL OF PREDATORY AQUATIC INSECTS IN NURSERY PONDS - Prasad, R R (Indian Journal of Fisheries, 2011)
The efficacy of kerosim oM in the contrail of aquatic insects causing considerabledamage to oaitip fry in the Hungary iponds has been tested and' foundequally good! with other existing methods